Prediction of the Population of Banda Aceh City Using the Laplace Transformation - Syafira, Nurul; Murida, Eva; Hanim, Safiatun; Yuni, Syarifah Meurah; Amri, Saiful; Hafnani, Hafnani; Nurmaulidar, Nurmaulidar (Transcendent Journal of Mathematics and Applications, 2024)
Population prediction is an estimate of the population in the future based on assumptions from the population growth rate. Based on data from the Central Statistics Agency (BPS), the population in Banda Aceh City is increasing every year with an average growth of around 2%. The purpose of this research is to predict the population in Banda Aceh City using the Laplace transformation on exponential model. The exponential model is a simple model to describe population growth patterns. Using Laplace transformation can easily get a difinitive analytic solution. The Laplace transformation of the exponential model is used to calculate the growth rate with data on the population of Banda Aceh City in 2015-2022. Based on the results of the study, the value of the growth rate (r) is obtained from determining the precentage error (MAPE) of each model to determine the predicted value that is closest to the actual value. So, model VII is the most accurate with a value (r) is 0,00412. The result of this study also show that model VII is used to predict the population in Banda Aceh City in 2030 when is 266.259 people.